2023
DOI: 10.3390/jcm12082882
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction: A Cellular and Molecular Hub in Pathology of Metabolic Diseases and Infection

Abstract: Mitochondria are semiautonomous doubly membraned intracellular components of cells. The organelle comprises of an external membrane, followed by coiled structures within the membrane called cristae, which are further surrounded by the matrix spaces followed by the space between the external and internal membrane of the organelle. A typical eukaryotic cell contains thousands of mitochondria within it, which make up 25% of the cytoplasm present in the cell. The organelle acts as a common point for the metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…On the other side, in infectious effusions, the detected biological processes were those involved in metabolic processes affecting ATP production, cellular respiration, and the electron transport chain. These are well-known phenomena in the presence of bacterial infection, since bacteria use components of the host’s internal environment to produce ATP through cellular respiration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, in infectious effusions, the detected biological processes were those involved in metabolic processes affecting ATP production, cellular respiration, and the electron transport chain. These are well-known phenomena in the presence of bacterial infection, since bacteria use components of the host’s internal environment to produce ATP through cellular respiration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…2). Several studies have identified mitochondrial dysfunction to impact epigenetic landscape of the nuclear genome [87,88]. Mitochondrial dysfunction and mtDNA damage could induce reversible or irreversible changes in nuclear genomic DNAm profiles and thus, has important implication in the pathogenesis of aging, cancer and a wide range of mitochondrial diseases [89,90].…”
Section: Drivers Of Epigenetic Changes During Aging and Cancersmentioning
confidence: 99%
“…Mitochondria are double membrane bound dynamic cell organelles that are power house for energy production and also prime source for ROS production [38]. In several diseases, the overproduction of ROS is associated with a decrease in ATP synthesis due to mitochondrial dysfunction which fail to maintain cellular energy [39].…”
Section: Knockdown Of Drp1 and Jnk Signaling In Loss Of Scrib Rnai Re...mentioning
confidence: 99%